Wychowanie przez estetykę. Idea antropozoficzna w wybranych dziełach Karola Homolacsa - Oboleńska, Diana (Humaniora. Czasopismo Internetowe, 2021)
The article is an attempt to grasp the concept of anthroposophical aesthetics. The ideas of Rudolf Steiner, the founder of anthroposophy, repeatedly touched the area of human creative activity. The anthroposophical activity (including lectures and publications) of Karol Homolacs, professor of the State Higher School of Artistic Industry and the Academy of Fine Arts in Krakow, seems to be an excellent example of the application of these ideas in theory and practice.